FRI0284 Preoperative Use of Biologic Agents is not an Independent Risk Factor for SSI and Delayed Wound Healing in Patients with Rheumatoid Arthritis. (10th June 2014) - Kadota, Y.; Nishida, K.; Hashizume, K.; Nakahara, R.; Kanazawa, T.; Ozawa, M.; Nasu, Y.; Harada, R.; Machida, T.; Ozaki, T.
Abstract : Background: The perioperative use of biologic DMARDs in patients with rheumatoid arthritis (RA) has potential risks for delayed wound healing and infectious complications. Surgeons are recommended to discontinue biologic DMARDs to reduce the risk of surgical site infection and delayed wound healing. The guidelines for periopetrative cessation periods of biologic DMARDs differ among countries, and a firm conclusion on this issue has not been reached. Objectives: The aim of the study was to review the incidence of delayed wound healing and surgical site infection (SSI) in patients with RA undergoing orthopedic surgery and to evaluate risk for postoperative complications using biologic DMARDs. Methods: We retrospectively investigated a total of 1029 elective orthopedic procedures for RA patients performed between January 2004 and December 2012 at two centers (Okayama University Hospital and Kurashiki Kosai Hospital). Identification of SSI was done based on the 1999 guidelines for prevention of surgical site infection 1) .Cases which removed suture longer than 2 weeks after surgery or required resuture were regarded as delayed wound healing. Risk factors for SSI and delayed wound healing were analyzed by logistic regression analysis between age, BMI, disease duration, operative procedure, corticosteroid use, diabetes mellitus, hypertension, cardiovascular disease, and use of non biologic and biologic DMARDs. Results: In total 1039 procedures, SSIs and delayed wound healing were identified in 19 cases (1.83%) and 17 cases (1.64%), respectively. Superficial infection and deep infection were identified in 9 cases and 10 cases, respectively. One case of superficial infection and 4 cases of delayed wound healing were recorded in 198 procedures in patients using biologic agents including infliximab, etanercept, adalimumab, and tocilizumab. Foot surgery (OR 3.104, 95% CI 1.226-7.857), and age at the surgery (OR 1.064, 95% CI 1.010-1.117) were associated with increased risk of SSI. Total knee arthroplasty (OR 3.051, 95% CI 1.139-8.178) and disease duration (OR 1.003, 95% CI 1.000-1.006) were associated with increased risk of delayed wound healing. The preoperative use of biologic agents did not constitute an independent risk factor for SSI and delayed wound healing. Conclusions: In the current case-control study, the results suggest that biological agents are not risk factors for a significant increase of postoperative complications. However, more data are clearly needed and further prospective studies must be performed to confirm this finding. References: Mangram AJ, Horan TC, Pearson ML, Silver LC, Jarvis WR. Guideline for prevention of surgical site infection, 1999. Hospital infection control practices advisory committee. Infect Control Hosp Epidermal. 1999;20:250–78. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.5243